2022
DOI: 10.1002/jgc4.1565
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging electronic health records to inform genetic counseling practice surrounding psychiatric disorders

Abstract: Since nearly one‐fifth of US adults have a psychiatric disorder, genetic counselors (GCs) will see many patients with these indications. However, GCs’ reports of inadequate preparation and low confidence in providing care for patients with psychiatric disorders can limit their ability to meet patient's needs. How frequently psychiatric disorders present in GC sessions is currently unclear. Here, we used deidentified electronic health records (EHR) to estimate the prevalence of 16 psychiatric disorders. In 7,15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A second major barrier to PGC identified is that genetic counselors lack confidence in providing PGC. Other studies have suggested barriers to providing PGC may relate to: (1) limited training in PGC, (2) stigma associated with mental illness, (3) balancing existing workload demands, (4) lack of genetic testing, and (5) multifactorial nature of these psychiatric illnesses (Austin et al, 2008; Austin & Honer, 2005; Booke et al, 2020; Inglis et al, 2015; Low et al, 2018; Moldovan et al, 2017; Richter et al, 2022; Rowlatt et al, 2022). These barriers likely contribute to genetic counselors low confidence in the provision of PGC and warrant further investigation in the local setting.…”
Section: Discussionmentioning
confidence: 99%
“…A second major barrier to PGC identified is that genetic counselors lack confidence in providing PGC. Other studies have suggested barriers to providing PGC may relate to: (1) limited training in PGC, (2) stigma associated with mental illness, (3) balancing existing workload demands, (4) lack of genetic testing, and (5) multifactorial nature of these psychiatric illnesses (Austin et al, 2008; Austin & Honer, 2005; Booke et al, 2020; Inglis et al, 2015; Low et al, 2018; Moldovan et al, 2017; Richter et al, 2022; Rowlatt et al, 2022). These barriers likely contribute to genetic counselors low confidence in the provision of PGC and warrant further investigation in the local setting.…”
Section: Discussionmentioning
confidence: 99%